Creating plugins to extend WordPress : developing custom plugins with PHP and the WordPress API - Chellman, Joe (O'Reilly, 2015)
"In this Creating Plugins to Extend WordPress training course, expert author Joe Chellman will teach you how to create your own plugins using the WordPress API. This course is designed for users that already have a basic working knowledge of WordPress. You will start by learning about the highlights of the WordPress API, then jump into creating your first plugin: a dashboard banner. From there, Joe will teach you how to create your second plugin, as well as how to further enhance your plugin, including how to create a widget for custom posts, register settings and sections, and prepare your plugin for localization. This video tutorial also covers additional plugin possibilities, such as using transients to cache expensive operations, implementing the transients API, and reacting to deactivation and uninstallation of your plugin. Finally, you will learn how to distribute your plugin, including how to publish independently on GitHub and submit to the WordPress.org plugin directory. Once you have completed this computer based training course, you will have learning how to create and distribute your own plugins using PHP and the WordPress API."--Resource description page.